2008
DOI: 10.1182/blood-2008-03-146415
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic modeling of human RBC alloimmunization: evidence for a distinct population of immunologic responders

Abstract: Red blood cell (RBC) transfusion is unique as a common large-scale intravenous introduction of foreign tissue and provides a valuable opportunity to study human immunologic response to intravenous foreign antigen. Patients receiving RBC transfusions are at risk of forming alloantibodies against donor RBC antigens, and valid estimates of alloimmunization risk are clinically important, but little is known about the factors governing this risk or, more generally, about determinants of human response to intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
170
1
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(186 citation statements)
references
References 14 publications
2
170
1
13
Order By: Relevance
“…Relatively low alloimmunization rates were found in populations with little exposure, higher rates at increased exposures and the majority of antibodies appear to be formed before 20 RBC units or less [7,8,28,29,38]. A subgroup of patients appears to alloimmunize after only limited exposure while a significant proportion of patients remains unaffected despite numerous transfusions [39,40]. Moreover, we found that the risk of second alloantibody formation appears to be higher compared to first alloimmunization.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Relatively low alloimmunization rates were found in populations with little exposure, higher rates at increased exposures and the majority of antibodies appear to be formed before 20 RBC units or less [7,8,28,29,38]. A subgroup of patients appears to alloimmunize after only limited exposure while a significant proportion of patients remains unaffected despite numerous transfusions [39,40]. Moreover, we found that the risk of second alloantibody formation appears to be higher compared to first alloimmunization.…”
Section: Discussionmentioning
confidence: 61%
“…We provide further evidence for an increased risk of alloimmunization in SCD compared to the general population, independent of the cumulative transfusion exposure [5,6,11,39,41]. This susceptibility for alloimmunization in SCD has previously been explained by the antigenic differences between donors and recipients, SCD specific factors such as chronic inflammation and patient-related factors such as genetic background [2].…”
Section: Discussionmentioning
confidence: 80%
“…There is similar evidence for the existence of two distinct immunological response groups to transfusion in humans. Whereas some patients develop alloantibodies after receiving a relatively small number of transfusions (responder phenotype), others may never become alloimmunized despite a large number of RBC antigen exposures (non-responder phenotype) (Higgins & Sloan, 2008). By including only SCD patients with at least one RBC alloantibody, we were more likely to include a group of patients likely to have co-expression of other immunogenetic modifiers that may increase alloimmunization potential.…”
Section: Discussionmentioning
confidence: 99%
“…The proper selection of antigen-negative RBCs for regular transfusion patients can minimize the risk of alloimmunization as some of these blood group antigens can stimulate clinical significance antibodies and cause transfusion reaction. The blood group antigens that are usually implicated are Rhesus, Kell, Kidd and Duffy (Higgins & Sloan, 2008;Klein & Anstee, 2006;Transfusion, 2014). Once alloantibodies were developed, the management of thalassaemia patients will become more complicated as the antibodies will limits the availability as well as the safety of subsequent RBC transfusion (George, 2013).…”
Section: Discussionmentioning
confidence: 99%